Upaya praktik Good Corporate Governance dalam penghindaran pajak di Indonesia - Budi Chandra; Cintya Cintya (Jurnal Ekonomi Modernisasi, 2021)
Tax avoidance is done by looking for the weeknesses in the lawsand regulations. This action occurs none other than caused by corporate governance. The purpose of this research is to determine the relationship between good corporate governance and tax avoidance. Good corporate governance is proxied by board gender diversity, institutional ownership, audit committee and independence commissioners. The sample used in this research contains annual reports taken from 111 companies listed in Indonesian Stock Exchange in 2016-2020. The data that has been collected is then processed using a data panel regression analysis system. The result shows there is a significant negative relation between audit committee and tax avoidance. Board gender diversity, institutional ownership and independent commissioners are negatively affect tax avoidance but not statistically significant. In addition, the control variables in the form of leverage and firm size are proven to have a significant negative and positive effect towards tax avoidance. Meanwhile, ROA is not proven to have a significant influence on tax avoidance. The recommendation from this research is that the next researcher should add the number of sample data and variables outside of this study in order to get better research results.